2016
DOI: 10.5194/amt-9-1361-2016
|View full text |Cite
|
Sign up to set email alerts
|

Dimensioning IRGA gas sampling systems: laboratory and field experiments

Abstract: Abstract. Both laboratory and field experiments were carried out in order to define suitable configuration ranges for the gas sampling systems (GSSs) of infrared gas analyzers (IRGAs) used in eddy covariance measurements.In the laboratory, an original dynamic calibration bench was developed in order to test the frequency attenuation and pressure drop generated by filters. In the field, three IRGAs of the same type equipped with different filters or different rain caps were installed and run and the real freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Laboratory evaluation of the LGR time response (Fig. S4) gives an e-fold flush time of 90 ± 16 ms, or an effective cutoff frequency (following the definition of Aubinet et al, 2016) of 3.8 Hz. A Picarro G1301-m analyzer supplies an additional set of CO 2 / CH 4 / H 2 O mixing ratios.…”
Section: Greenhouse Gas (Ghg) Suitementioning
confidence: 99%
“…Laboratory evaluation of the LGR time response (Fig. S4) gives an e-fold flush time of 90 ± 16 ms, or an effective cutoff frequency (following the definition of Aubinet et al, 2016) of 3.8 Hz. A Picarro G1301-m analyzer supplies an additional set of CO 2 / CH 4 / H 2 O mixing ratios.…”
Section: Greenhouse Gas (Ghg) Suitementioning
confidence: 99%
“…Rannik et al (2015) found a disagreement of almost a factor of 2 in the N 2 O and CO 2 time constants for a system that measured both gases, opting to use the value measured for CO 2 for spectral corrections of both gases. However, it is difficult to directly compare the absolute values of the frequency-response τ e with the commonly used cospectra method (Detto et al, 2011;Peltola et al, 2014;Rannik et al, 2015;Aubinet et al, 2016). The cospectral method is highly dependent on the adherence of the spectra to similarity scaling and is also affected by sensor separation and by imperfect synchronization of the scalar with vertical wind.…”
Section: Discussionmentioning
confidence: 99%
“…High-frequency concentration fluctuations can be attenuated by line averaging within the sample cell, as well as sample mixing within various system components, such as intake tubing, dryers, filters, and rain caps (Moore, 1986;Massman, 2000). Analyzer frequency response often represents a significant proportion of the total high-frequency losses (Horst, 1997;Kroon et al, 2010b), but these sampling system components may also significantly degrade system frequency response (Aubinet et al, 2016). Modern closed-path analyzers for CO 2 EC fluxes achieve high-frequency response with low-power pumps by using small sample cells (6 or 16 mL) that operate near ambient pressure (Burba et al, 2010;Novick et al, 2013).…”
Section: S E Brown Et Al: Evaluation Of a Lower-powered Analyzermentioning
confidence: 99%
See 1 more Smart Citation
“…The LICOR sensors in different forms are used at automated field stations for research networks covering large temporal and spatial scales, and they are therefore well characterised concerning the transfer function of different components (Metzger et al, 2016). The closed-path sensors requiring a gas sampling system can be affected by high-frequency attenuation, so inlets and tubes have to 30 be dimensioned reasonably (Aubinet et al, 2016;Metzger et al, 2016).…”
mentioning
confidence: 99%